2004
DOI: 10.1641/0006-3568(2004)054[0843:acftdl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework to Develop Long-Term Ecological Research and Management Objectives in the Wider Caribbean Region

Abstract: R ecent reviews describing human impacts on coastal and marine ecosystems in the Caribbean emphasize two major problems. First is the lack of information about processes controlling the productivity of diverse coastal ecosystems. Second is the potential long-term negative impact of human disturbances on the goods and services these ecosystems provide (Richards and Bohnsack 1990, Ogden 1997). The Caribbean Sea has been diagnosed as an ecosystem showing "signs of environmental stress" (Richards and Bohnsack 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 54 publications
(55 reference statements)
0
34
0
2
Order By: Relevance
“…Fertilization experiments in several such old-growth scrub mangrove stands have demonstrated that they are nutrient limited and that addition of the limiting nutrient dramatically increased their productivity and converted their stunted physiognomy to resemble more vigorously growing trees in fringing mangrove forests (Feller 1995, Feller et al 2003a, b, Lovelock et al 2006, Martin et al 2010. Although the aboveground biomass in scrub mangroves is low compared to other types of mangrove forests, these low-stature forests are widespread and have been documented to dominate much of the mangrove landscape not only at our study site along the IRL (Feller et al 2003b), but also in south Florida (Ross et al 2001, Simard et al 2006, Belize (Murray et al 2003, Rodriguez and, Panama (Lovelock et al 2005), and throughout the Caribbean (Rivera- Monroy et al 2004).…”
Section: Discussionmentioning
confidence: 69%
“…Fertilization experiments in several such old-growth scrub mangrove stands have demonstrated that they are nutrient limited and that addition of the limiting nutrient dramatically increased their productivity and converted their stunted physiognomy to resemble more vigorously growing trees in fringing mangrove forests (Feller 1995, Feller et al 2003a, b, Lovelock et al 2006, Martin et al 2010. Although the aboveground biomass in scrub mangroves is low compared to other types of mangrove forests, these low-stature forests are widespread and have been documented to dominate much of the mangrove landscape not only at our study site along the IRL (Feller et al 2003b), but also in south Florida (Ross et al 2001, Simard et al 2006, Belize (Murray et al 2003, Rodriguez and, Panama (Lovelock et al 2005), and throughout the Caribbean (Rivera- Monroy et al 2004).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, although this species can be globally classified in the Least Concern category (IUCN 2003), their conservation status can be expected to decline rapidly in the future as wetland environments are disappearing at a fast rate both in Africa and the Caribbean Basin because of extensive urban and agricultural developments (Rivera-Monroy et al 2004;Thieme et al 2005;Keddy et al 2009). Indeed, the main difficulty of our study was to find wild populations in the Caribbean and Africa.…”
Section: Systematic and Conservation Implicationsmentioning
confidence: 99%
“…Most large-scale freshwater diversions have been implemented in temperate latitudes whereas the number of diversions in tropical latitudes is limited mainly due to their engineering cost (Cloern 2001;Rivera-Monroy et al 2004a;Sklar et al 2005;Junk et al 2006). One of few large freshwater diversion projects in the neotropics was implemented to rehabilitate mangrove wetlands and fisheries in the Ciénaga Grande de Santa Marta (CGSM), the largest coastal lagoon (450 km 2 ) in the Caribbean region of Colombia.…”
Section: Introductionmentioning
confidence: 99%